The effects of selected marketing mix activities on brand equity - Ng, Lee Chin (2004)
Branding has never been more important than in a competitive environment. Branding is the process of creating an association between symbol / object / emotion / perception and a product / company with the goal of driving loyalty and creating differentiation. The importance of the concept of brand equity has been on the rise. The dimension of brand equity consists of (i) perceived quality, (ii) brand loyalty, (iii) brand awareness, (iv) brand associations and (iv) other proprietary brand assets. There is no question that a strong brand is an important corporate asset. Brand equity however cannot be measured in dollars and cents but rather, it is a direct result of how consumers value a brand based on their experiences and perceptions. It is these experiences and perceptions that permit the brand to earn greater volume or margins than it could without the brand name. These experiences and perceptions are built through carefully planned and executed marketing mix activities.This dissertation explores the relationship between selected marketing mix activities and the dimension of brand equity. Not all marketing mix activities carried out by the company will have a positive effect on the dimension of the brand equity. These dimensions (if they have a positive effect) are then related to brand equity. Two companies (Unilever and Procter & Gamble) have been selected for the purpose of this dissertation. The results show that the key determinants of marketing mix activities that build brand equity are dominant brand reputation, effective and repetitive advertising, competitive pricing, strong product penetration, and occasional price promotion.